Knowledge and Attitude Relationship on Clean and Healthy Lifestyle Towards The Prevention of Covid-19 Transmission in RW.03 Ciganjur Village South Jakarta - Saputri, Milla Evelianti; Suharyanto, Toto; Khumaera, Dhea (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
The coronavirus disease 2019 (COVID-19) originating from Wuhan, China began to emerge in December 2019. Until now, COVID-19 has become a global pandemic, and Indonesia has been one of the countries that affected by this virus since March 2020. Based on World Health Organization data on October 20, 2020, corona has spread in 215 countries and has infected 40.4 million people. And based on data from the Indonesian Task Force for Covid-19, the victims who have been infected have reached 369,000 people. This study aims to determine whether there is a relationship between knowledge and attitudes about Clean and Healthy Behavior towards the prevention of COVID-19 in RW.03 Ciganjur Sub-District. The sample in this study amounted to 97 respondents in RW.03 Ciganjur Sub-District. The sampling technique used was simple random sampling and the data were analyzed using Chi-Square. The results showed that there was a relationship between knowledge about clean and healthy behaviors against the prevention of COVID-19 transmission, indicated by a p value of 0.000 (p